Nitrogen fertilization and of N2O emission in corn production in the Comarca Lagunera - García Sepúlveda, Jorge Luis; Cueto Wong, José Antonio; Báez Pérez, Aurelio; Saynes Santillán, Vinisa (Revista Mexicana de Ciencias Agrícolas, 2021)
An experiment was established to quantify the level of N2O emissions in the soil in response to the application of increasing doses of nitrogen fertilization for corn production. The treatments were as follows: 1) control, without application of nitrogen (N); 2) application of 200 kg ha-1 of N; 3) application of 400 kg ha-1 of N. An experimental design in random blocks with three repetitions was used. The corresponding treatments with forage corn were established in July 2018. To carry out the measurements of N2O emissions, two PVC static chambers were placed in each experimental unit: one at the ridge (B), where the fertilizer was applied, and another at the bottom of the furrow (F). Periodic measurements were carried out and at the same time soil samples from 0 to 15 cm deep were collected to measure moisture content and inorganic N (N-NO3- + N-NH4+) and soil temperature. The content of inorganic N of the soil fluctuated on average from 28 to 59 mg kg-1 of soil and the flux of N2O emissions fluctuated from 22 to 60 g ha-1 day-1. Both were closely related to the increasing doses of nitrogen fertilization, both at the ridge and at the bottom of the furrow, the R2 fluctuated between 0.81 and 0.99. The trend was adjusted to an exponential model. Dry forage and grain production reached 17.5 and 9.6 t ha-1, respectively, with the highest nitrogen fertilization dose. There were no significant differences (p< 0.05) between 200 and 400 units of N ha-1, which indicated a low utilization of N by the crop and a higher emission of N2O with the latter.
Keywords: greenhouse gas emission; fertilization; soil nitrogen